(untitled) (Revista Ciência Agronômica, 2020)
This study aimed to develop PCR assays, reaction combinations, and validation of tetranucleotide SSR loci for tilapia, to minimize the impact of erroneous allele inferences on genotype determination of this marker. Microsatellites containing tetranucleotide repeats were obtained from tilapia genome, version 2.1, avoiding loci in the same linking group. Primers were designed for different fragment sizes, and fluorescence added to each locus. A total of 10 loci were amplified, separately and in combination, and loaded into a single capillary sequencer panel. Alleles were amplified without stutters and easily interpreted. PCR amplifications of DNA repeatedly extracted from samples, and genotyping at different PCR rounds were performed to infer allele signaling errors. The panel obtained in this study is currently used in kinship analyses and pedigree corrections in a tilapia breeding program.